Aplikasi Deteksi Suhu dan Orang untuk Ruang Server dengan Raspberry PI - Giantara, Markus Daud; Santoso, Leo Willyanto (Jurnal Infra, 2018)
Server room is room which is store server, networking hardware, etc. A server room must have standard security which is can protect devices like temperature of server room, humidity server room, fire, access to the entry of people who are considered less responsible.Lack of control and monitoring of room temperature and humidity are common. This is due to lack of supervision or control of the staff or admin of the server room. If the temperature and humidity of the server room is uncontrolled then hardware inside the room can be broke or the performance of the server devices can be decrease. Often the security of the server room from the reach of less responsible people is also under-scrutiny. So sometimes there are people who can enter into the server room without knowing the intent and its purpose.The solution to this problem is to use a room monitoring application, which can be used to control and monitor temperature and humidity in the server room, so that the temperature and humidity of the server room can be maintained. This app can also prevent unauthenticated people from entering the server room.